1994
DOI: 10.2343/geochemj.28.199
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical implications of subaqueous molten sulfur at Yugama crater lake, Kusatsu-Shirane volcano, Japan.

Abstract: Crater lakes with active subaqueous fumaroles often contain molten sulfur pools on the lake floor. Volcanic gases passing through the sulfur pools carry hollow spherules of solidified molten sulfur to the surface of crater lakes. This sulfur dissolves SO2 and H2S gases and releases these gases into the water. The sulfur also contains homocyclic sulfur (cycl. S, x = 6-16) and probably sulfane monosulfonates. The concentration of cyclic S7 increases with increasing temperature between 120 and 175°C, which is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 35 publications
8
57
0
1
Order By: Relevance
“…A decrease in polythionate (S 4 O 2− 6 , S 6 O 6 ) concentrations was observed also at Ruapehu's Crater Lake during very low temperatures for 3 months in 1988 prior to the Dec. 8, 1988 unheralded eruption (Takano et al, 1994). This apparently indicated that the liquid S e pool under the lake remained open to fumarolic degassing (H 2 S and SO 2 ) even during periods of low lake temperatures, and therefore it could not be a barrier for magmatic heat transfer.…”
Section: Crater Lakes As Sensitive Indicators Of S Viscositymentioning
confidence: 98%
See 4 more Smart Citations
“…A decrease in polythionate (S 4 O 2− 6 , S 6 O 6 ) concentrations was observed also at Ruapehu's Crater Lake during very low temperatures for 3 months in 1988 prior to the Dec. 8, 1988 unheralded eruption (Takano et al, 1994). This apparently indicated that the liquid S e pool under the lake remained open to fumarolic degassing (H 2 S and SO 2 ) even during periods of low lake temperatures, and therefore it could not be a barrier for magmatic heat transfer.…”
Section: Crater Lakes As Sensitive Indicators Of S Viscositymentioning
confidence: 98%
“…Pure sulfur viscosity is highly temperature dependent, but also extremely sensitive to the presence of impurities (Bacon and Fanelli, 1943;Meyer, 1976). This has been noted in volcanic settings (Takano, 1987;Rowe et al, 1992;Takano et al, 1994), but not followed up. Experiments carried out in the early 1940's (Bacon and Fanelli, 1943) showed that organic material, trivalent elements, ammonia, halogens, or the exposure to certain gases (e.g., H 2 S), almost always lead to lower viscosities on heating than for the pure S e case.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations